A flexible soft magnetic ferrite composite film material for energy storage battery state detection and a preparation method thereof

By oriented NiCuZn soft magnetic ferrite nanowires within a flexible substrate, a polyaniline-coated core-shell nanowire precursor was prepared, solving the problems of weak magnetic induction performance and insufficient mechanical strength of existing flexible soft magnetic ferrite thin film materials, and realizing efficient high-frequency current signal detection and stable monitoring.

CN123026401APending Publication Date: 2026-11-03CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611148428.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing flexible soft magnetic ferrite thin film materials have weak magnetic induction performance in energy storage battery state detection, making it difficult to efficiently capture high-frequency current signals. In addition, their mechanical strength is insufficient, making them unable to meet the long-term stable monitoring requirements of complex operating environments.

Method used

A core-shell structured nanowire precursor coated with polyaniline was prepared by using NiCuZn soft magnetic ferrite nanowires oriented in a single direction within a flexible matrix, through interfacial polymerization and high-temperature sintering. The precursor nanowires were then oriented in an applied magnetic field to form a flexible soft magnetic ferrite composite thin film material.

Benefits of technology

It improves the magnetic induction ability and signal coupling efficiency of the material, enhances mechanical stability, is suitable for installation and testing on complex curved battery surfaces, and improves the detection sensitivity and reliability of high-frequency current signals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123026401A_ABST
    Figure CN123026401A_ABST
Patent Text Reader

Abstract

The application discloses a flexible soft magnetic ferrite composite film material for energy storage battery state detection and a preparation method thereof, and belongs to the technical field of energy storage battery safety monitoring and sensing material. The preparation method comprises the following steps: preparing superfine NiCuZn ferrite precursor nanoparticles by means of a sol-gel method combined with trace V and Ca element doping; adopting an interfacial polymerization method to synthesize core-shell structure nanowire precursors with polyaniline as a shell and ferrite particles as a core under the induction of an applied magnetic field; obtaining well-crystallized NiCuZn ferrite nanowires through segmented high-temperature sintering; and mixing the nanowires with a PDMS prepolymer, and making the nanowires directional arrangement and solidification under the applied magnetic field. The composite film prepared by the application has excellent flexibility, high-frequency magnetic performance, high magnetic induction intensity and good mechanical strength, can be closely attached to the surface of a to-be-detected object, significantly improves the coupling and detection precision of high-frequency current signals, and is suitable for early safety early warning of the internal state of an energy storage battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the interdisciplinary field of energy storage battery safety status detection technology and sensing materials, specifically a flexible soft magnetic ferrite composite thin film material for energy storage battery status detection and its preparation method. Background Technology

[0002] With the rapid development of the energy storage industry, the safe operation of energy storage batteries has received increasing attention, and accurate assessment of their safety status is crucial to ensuring the reliable operation of energy storage systems. Currently, assessing the status based on the high-frequency current signal generated by the battery itself is an effective non-invasive monitoring method. This method can provide early warnings of safety hazards such as internal short circuits, aging, and thermal runaway by detecting the high-frequency current signal generated inside the battery. In this technical approach, the sensing device, as the core component for signal acquisition and transmission, directly determines the accuracy of the safety status assessment. Among numerous sensing materials, soft magnetic ferrite materials, with their excellent electromagnetic properties, wide bandwidth spectral characteristics, and low power loss characteristics, have become an important component in constructing sensing devices for energy storage battery safety status assessment, providing material support for the efficient sensing and conversion of high-frequency current signals.

[0003] However, traditional soft magnetic ferrite materials are mostly rigid structures, making it difficult to achieve sufficient and close contact with the surface of the object under test in practical applications. This results in low signal coupling between the sensing device and the object under test, affecting the accuracy of high-frequency current signal acquisition and limiting the reliability of safety status assessment. To address the low coupling efficiency of rigid materials, research and development of flexible soft magnetic ferrite thin films has been initiated. Existing flexible products are mostly based on magnetic rubber cores or nanocrystals. Although these flexible films possess certain bendability characteristics, which can improve the fit with the object under test to some extent, they still have significant shortcomings in core performance: 1) Its magnetic induction performance is relatively weak, making it difficult to achieve efficient capture of high-frequency current signals; 2) Poor high-frequency characteristics, unable to meet the detection requirements of high-frequency current signals from energy storage batteries; 3) Insufficient mechanical strength makes it prone to deformation, damage and aging during installation and use, affecting the service life and stability of the sensing device, and making it difficult to adapt to the complex operating environment of energy storage batteries and the requirements of long-term stable monitoring.

[0004] The aforementioned defects make it difficult for existing flexible soft magnetic ferrite films to meet the stringent requirements for sensing materials in energy storage battery state monitoring, thus limiting the further development of energy storage battery safety status assessment technology. Summary of the Invention

[0005] The purpose of this invention is to provide a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection and its preparation method, so as to at least solve the technical problem of weak magnetic induction performance of traditional soft magnetic ferrite materials.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection, which is composed of a magnetic functional phase and a flexible matrix. The magnetic functional phase is NiCuZn soft magnetic ferrite nanowires oriented in a single direction within the flexible matrix. The mass percentage of the NiCuZn soft magnetic ferrite nanowires to the flexible matrix is ​​(40-65)%: (35-60)%.

[0007] A further improvement of the present invention is that the flexible matrix is ​​polydimethylsiloxane.

[0008] A further improvement of the present invention is that the transmission impedance of the flexible soft magnetic ferrite composite thin film material is greater than 5mV / mA ​​in the range of 0-100MHz.

[0009] In a second aspect, the present invention provides a method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection, comprising: Preparation of ultrafine NiCuZn ferrite precursor nanoparticles; Using aniline monomer and the ultrafine NiCuZn ferrite precursor nanoparticles as raw materials, and ammonium persulfate as an initiator, a polyaniline-coated core-shell structured soft magnetic ferrite nanowire precursor was prepared by interfacial polymerization reaction at the oil-water interface under the condition of an applied external magnetic field. The core-shell structured soft magnetic ferrite nanowire precursor was sintered at high temperature to obtain NiCuZn soft magnetic ferrite nanowires. The NiCuZn soft magnetic ferrite nanowires are dispersed in a flexible matrix, and an external magnetic field is applied to orient the nanowires. The nanowires are then cured to obtain the flexible soft magnetic ferrite composite film material for energy storage battery state detection. The mass percentage of the NiCuZn soft magnetic ferrite nanowires to the flexible matrix is ​​(40-65)%: (35-60)%.

[0010] A further improvement of the present invention is that the PDMS prepolymer is described.

[0011] A further improvement of this invention is that the step of preparing ultrafine NiCuZn ferrite precursor nanoparticles specifically includes: Weigh out nickel nitrate, copper nitrate, zinc nitrate, ferric nitrate, and bismuth nitrate, dissolve them in deionized water, and adjust the pH to below 2 to obtain mixture A; Add an alkaline solution to mixture A to adjust the pH to 3.0, thus obtaining mixture B; Vanadium pentoxide and calcium oxide were added to mixture B, stirred and dispersed, and then heated at 60-80℃ to form a sol. After drying, a dry gel was obtained. The dry gel was sintered and then ball-milled to obtain the ultrafine NiCuZn ferrite precursor nanoparticles.

[0012] A further improvement of the present invention is that the molar percentages of nickel nitrate, copper nitrate, zinc nitrate, iron nitrate, bismuth nitrate, vanadium pentoxide, and calcium oxide are 6.3%, 6.4%, 21.6%, 63.8%, 1.2%, 0.5%, and 0.2%, respectively; and the molar ratio of citric acid to the total metal ions in mixture A is 1.2:1.

[0013] A further improvement of this invention is that the step of preparing a polyaniline-coated core-shell structured soft magnetic ferrite nanowire precursor by means of an interfacial polymerization reaction using aniline monomer and the ultrafine NiCuZn ferrite precursor nanoparticles as raw materials, ammonium persulfate as an initiator, and an external magnetic field at the oil-water interface, specifically includes: Aniline monomer and the ultrafine NiCuZn ferrite precursor nanoparticles were dispersed in cyclohexane to form an oil phase D; ammonium persulfate was dissolved in deionized water to form an aqueous phase E; the oil phase D was injected into the aqueous phase E to form an interface, and the reaction was allowed to proceed under an external magnetic field of 0.1T-0.5T at 0-5℃ for 2-4 hours; after the reaction, the precursor was washed and dried to obtain the polyaniline-coated core-shell soft magnetic ferrite nanowire.

[0014] A further improvement of this invention is that, in the step of obtaining NiCuZn soft magnetic ferrite nanowires by high-temperature sintering of the core-shell structured soft magnetic ferrite nanowire precursor, the high-temperature sintering is a segmented heat treatment: first, the temperature is increased from room temperature to 300℃ at a rate of 0.5-1℃ / min and held for 1 hour; then, the temperature is increased to 400℃ at the same rate and held for 2 hours; then, the temperature is increased to 500℃ at a rate of 0.5℃ / min and held for 2-4 hours; finally, the temperature is increased to 850℃ at a rate of 1-3℃ / min and held for 1-2.5 hours; followed by furnace cooling.

[0015] A further improvement of this invention is that the following steps are involved: dispersing the NiCuZn soft magnetic ferrite nanowires in a flexible substrate, applying an external magnetic field to orient the nanowires, and then curing them to obtain the flexible soft magnetic ferrite composite film material for energy storage battery state detection. Specifically, this includes: uniformly mixing the NiCuZn soft magnetic ferrite nanowires with a flexible substrate at a mass fraction of (40-65)% and (35-60)% to obtain a mixed slurry; injecting the slurry into a mold and placing it in a uniform external magnetic field of 0.8-2.0T for 2-4 hours to orient the nanowires; then placing the mold in a vacuum drying oven at 60-80℃ for 2-5 hours to cure, and finally demolding to obtain the flexible soft magnetic ferrite composite film material for energy storage battery state detection.

[0016] A further improvement of the present invention is that the molar ratio of the aniline monomer to the ultrafine NiCuZn ferrite precursor nanoparticles is (0.8-1.25):1; and the molar ratio of the aniline monomer to the ammonium persulfate is 1:1.1.

[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention employs NiCuZn soft magnetic ferrite nanowires oriented in a single direction within a flexible matrix as the magnetic functional phase, and controls the mass percentage of NiCuZn soft magnetic ferrite nanowires to the flexible matrix. This allows the composite thin film material to form a relatively ordered magnetic response structure while maintaining flexible adhesion, which is beneficial for improving the material's magnetic induction capability and signal coupling efficiency for high-frequency current signals from energy storage batteries. Simultaneously, this ratio range achieves a good balance between the content of magnetic filler and the content of flexible matrix, giving the material good magnetic properties, flexibility, and mechanical stability, making it suitable for energy storage battery state monitoring scenarios.

[0018] Furthermore, in this invention, the flexible substrate is polydimethylsiloxane (PDMS), which can utilize the good flexibility, elastic recovery ability and molding performance of PDMS to enable the composite film material to better adhere to the surface of the energy storage battery or the object being detected, reducing signal coupling loss caused by insufficient adhesion of rigid materials; at the same time, the PDMS substrate can provide flexible support and coating environment for NiCuZn soft magnetic ferrite nanowires, which is beneficial to improving the structural stability of the composite film during installation, bending and long-term use.

[0019] Furthermore, by limiting the transmission impedance of the flexible soft magnetic ferrite composite film material to be greater than 5mV / mA ​​in the 0-100MHz frequency range, this invention ensures that the material has a relatively stable signal response capability in the high-frequency current signal detection band of energy storage batteries, which is beneficial to improving the detection sensitivity and effective acquisition capability of high-frequency current signals. This transmission impedance characteristic enables the composite film material to meet the requirements for high-frequency signal capture in energy storage battery state detection, thereby helping to improve the reliability of early identification of abnormal states inside energy storage batteries.

[0020] This invention utilizes a sol-gel method to prepare ultrafine NiCuZn ferrite precursor nanoparticles, an interfacial polymerization method to prepare a polyaniline-coated core-shell soft magnetic ferrite nanowire precursor, and a high-temperature sintering method to obtain NiCuZn soft magnetic ferrite nanowires. An external magnetic field is applied to a flexible matrix to orient the nanowires before curing. This method enables continuous and controllable preparation from precursor particles and nanowire structures to the oriented structure of the composite film. It is beneficial for obtaining soft magnetic ferrite nanowire composite films with relatively uniform morphology and good orientation, thereby improving the magnetic permeability, magnetic induction performance, high-frequency response capability, and mechanical properties of the composite material.

[0021] Furthermore, by using PDMS prepolymer as a flexible matrix material during the preparation process, this invention can provide a flowable and dispersible mixed system for NiCuZn soft magnetic ferrite nanowires before curing, which is beneficial for the nanowires to be oriented and aligned under the action of an external magnetic field. After subsequent curing, the PDMS prepolymer forms a flexible matrix and fixes the orientation state of the nanowires, thereby helping to maintain the ordered magnetic pathway structure inside the composite film and improving the flexibility, adhesion and stability of the film.

[0022] Furthermore, this invention improves the dispersion uniformity and compositional consistency of each metal component in the precursor by dissolving nickel nitrate, copper nitrate, zinc nitrate, iron nitrate, and bismuth nitrate and adjusting the acidic environment during the preparation of ultrafine NiCuZn ferrite precursor nanoparticles, adding a citric acid system, and further introducing vanadium pentoxide and calcium oxide. This is followed by sol formation, drying, sintering, and ball milling. This step facilitates the acquisition of NiCuZn ferrite precursor nanoparticles with a more uniform particle size distribution, providing a material basis for subsequent interfacial polymerization to form nanowire precursors and sintering to obtain stable NiCuZn soft magnetic ferrite nanowires.

[0023] Furthermore, in this invention, the molar percentages of nickel nitrate, copper nitrate, zinc nitrate, iron nitrate, bismuth nitrate, vanadium pentoxide, and calcium oxide are 6.3%, 6.4%, 21.6%, 63.8%, 1.2%, 0.5%, and 0.2%, respectively. This allows for more precise control of the composition ratio and complexation reaction conditions of the NiCuZn ferrite precursor, which is beneficial for improving the uniformity of the precursor composition and the consistency of the subsequent sintering products. This ratio helps to obtain NiCuZn ferrite nanowires with good soft magnetic properties and provides compositional assurance for achieving high permeability, high magnetic induction intensity, and low power loss in composite films.

[0024] Furthermore, this invention disperses aniline monomers and ultrafine NiCuZn ferrite precursor nanoparticles in an oil phase and configures ammonium persulfate as an aqueous phase. Interfacial polymerization is carried out at the oil-water interface under low temperature and an applied magnetic field. This method utilizes interfacial confinement and magnetic field induction to promote the formation of core-shell structured nanowire precursors. This approach helps reduce the risk of disordered particle aggregation, improves the controllability and orientation basis of nanowire structure formation, and results in NiCuZn soft magnetic ferrite nanowires with better aspect ratio and structural continuity after subsequent sintering. This, in turn, helps improve the magnetic induction performance and mechanical reinforcement effect of the composite film.

[0025] Furthermore, by limiting the molar ratio of aniline monomer to ultrafine NiCuZn ferrite precursor nanoparticles and the molar ratio of aniline monomer to ammonium persulfate, this invention can control the amount of polyaniline generated, the degree of coating, and the reaction rate during the interfacial polymerization process. This is beneficial for forming a more uniform polyaniline coating layer and a stable core-shell structured nanowire precursor. This limitation can reduce the adverse effects of insufficient coating or overpolymerization on the formation of nanowire structures, improve the stability of the nanowire precursor morphology, and provide a guarantee for obtaining NiCuZn soft magnetic ferrite nanowires with a more complete structure in subsequent sintering.

[0026] Furthermore, this invention mixes NiCuZn soft magnetic ferrite nanowires with PDMS prepolymer at a specified mass fraction, and then cures them in a uniform external magnetic field of 0.8-2.0T for 2-4 hours before vacuum curing at 60-80℃ for 2-5 hours. This process can fully induce the nanowires to align along the magnetic field direction before curing and fix the oriented alignment structure after curing. This step is beneficial for constructing ordered magnetic pathways inside the composite film, improving the material's permeability, magnetic induction intensity, and high-frequency signal response capability. At the same time, the PDMS curing process imparts good flexibility, tensile strength, and bending adaptability to the film, enabling it to more stably adhere to the surface of the energy storage battery detection object and be used for high-frequency current signal detection.

[0027] This invention provides a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection and its preparation method. By improving the magnetic induction performance, high-frequency characteristics and mechanical properties of the flexible soft magnetic ferrite composite thin film material through material formulation and process, the performance requirements of the flexible soft magnetic ferrite composite thin film material for energy storage battery safety state detection are met.

[0028] This invention combines the sol-gel method with interfacial polymerization-sintering process to achieve controllable synthesis and surface modification of ferrite nanowires, thereby improving magnetocrystalline anisotropy and high-frequency magnetic response. This invention enables nanowires to be oriented and aligned in a PDMS matrix under an external magnetic field, thereby constructing an ordered magnetic pathway and significantly improving the magnetic permeability and magnetic induction intensity of the composite film. This invention uses PDMS as a flexible substrate and NiCuZn soft magnetic ferrite nanowires as magnetic fillers. The synergy of the two not only endows the composite material with good flexibility, but also the oriented NiCuZn soft magnetic ferrite nanowires effectively enhance the tensile strength and bending resistance of the composite material, significantly improving its mechanical properties. This gives the composite film material good bending properties, tensile recovery, and adhesion, making it suitable for installation and testing on complex curved battery surfaces.

[0029] Furthermore, existing soft magnetic ferrite composite materials are mostly hard materials sintered at high temperatures, and their dimensions are fixed during the production process. Their dimensions cannot be further adjusted according to the application during later use. This invention, however, disperses soft magnetic ferrite nanowires in a flexible substrate material to prepare a flexible thin film. The dimensions of this film can be flexibly adjusted according to the object being tested, thus achieving a closer fit and better signal coupling efficiency and detection level. The flexible soft magnetic ferrite composite thin film material provided by this invention for energy storage battery state detection can effectively adhere to the surface of the object under test, improving signal coupling efficiency and detection level, providing more reliable technical support for energy storage battery state detection, and is of great significance for ensuring the safe operation of energy storage power stations. Attached Figure Description

[0030] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 A schematic flowchart illustrating a method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection, provided in an embodiment of the present invention. Figure 2The images show the microstructure of the NiCuZn ferrite nanowires prepared in Examples 1-3 of this invention; where (a), (b), and (c) are the microstructures of the NiCuZn ferrite nanowires prepared in Examples 1, 2, and 3, respectively. Figure 3 The initial permeability and saturation magnetic induction of the flexible soft magnetic ferrite composite thin film material obtained in Examples 1-3 of the present invention are shown; wherein, (a) is a schematic diagram of saturation magnetic induction; and (b) is a schematic diagram of initial permeability. Figure 4 The coercivity and power loss of the flexible soft magnetic ferrite composite thin film material obtained in Examples 1-3 of the present invention are shown; wherein, (a) is a schematic diagram of coercivity; and (b) is a schematic diagram of power loss. Figure 5 This is a schematic diagram showing the transmission impedance results of the flexible soft magnetic ferrite composite thin film materials obtained in Examples 1-3 of the present invention; Figure 6 The diagram shows the mechanical properties of the flexible soft magnetic ferrite composite film materials obtained in Examples 1-3 of the present invention; wherein, (a) is a diagram showing the comparison of tensile strength; and (b) is a diagram showing the comparison of elongation at break. Detailed Implementation

[0031] The present invention will now be described in detail with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and features described herein can be combined with each other.

[0032] The following detailed description is exemplary and intended to provide further detailed explanation of the invention. Unless otherwise specified, all technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art. The terminology used in this invention is for describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention.

[0033] Please see Figure 1 As shown, in order to enable flexible soft magnetic ferrite composite thin film materials to possess both excellent magnetic induction performance and mechanical properties, thereby improving the high-frequency current signal capture capability and environmental adaptability of energy storage batteries, this invention provides a method for preparing flexible soft magnetic ferrite composite thin film materials for energy storage battery state detection, comprising the following steps: Step 1: Preparation of ultrafine NiCuZn ferrite precursor nanoparticles, specifically including: 1) Accurately weigh five nitrates according to molar percentage: Ni(NO3)2·6H2O (6.3%), Cu(NO3)2·3H2O (6.4%), Zn(NO3)2·6H2O (21.6%), Fe(NO3)3·9H2O (63.8%), and Bi(NO3)3·5H2O (1.2%), and mix them with deionized water. The molar ratio of total nitrates to deionized water is 1:10. Then, slowly add nitric acid solution to adjust the pH of the system to <2. Then, ultrasonically disperse the mixture at 50℃ for 30 minutes with an ultrasonic power of 200 W to obtain a homogeneous initial mixture A. 2) Accurately weigh citric acid according to the molar ratio of citric acid to total metal ions in the initial mixture A of 1.2:1, then dissolve it in deionized water with a molar ratio of citric acid to deionized water of 1:3, and then add it to the initial mixture A. Subsequently, add ammonia water dropwise to adjust the pH of the system to 3.0 to obtain mixture B. 3) Accurately weigh V2O5 (0.5%) and CaO (0.2%) according to the molar percentage and add them to the mixture B. After dispersing evenly by mechanical stirring, stir and heat the mixture at 60-80℃ for 3 hours to form a sol. Then transfer it to a vacuum drying oven to dry and obtain dry gel C. The drying temperature is 80℃ and the drying time is 4 hours. 4) The dry gel C was sintered at 400℃ for 3 hours, and then subjected to high-energy ball milling to obtain ultrafine NiCuZn ferrite precursor nanoparticles with uniform particle size distribution. The ball milling speed was 1200 r / min and the ball milling time was 4h.

[0034] Step 2: Prepare core-shell structured soft magnetic ferrite nanowire precursors using interfacial polymerization, specifically including: 1) The aniline monomer and the ultrafine NiCuZn ferrite precursor nanoparticles obtained in step 1 are dispersed in cyclohexane to form an oil phase D, wherein the molar ratio of aniline monomer to ultrafine NiCuZn ferrite precursor nanoparticles is (0.8-1.25):1. 2) Dissolve ammonium persulfate in deionized water to form aqueous phase E, wherein the molar ratio of aniline monomer to ammonium persulfate is 1:1.1; 3) Slowly inject the oil phase D into the aqueous phase E to form a clear oil-water interface. Apply a constant external magnetic field with a field strength of 0.1T-0.5T at a low temperature of 0-5℃ and let it stand for 2-4 hours. 4) After the reaction is complete, the product is repeatedly washed and filtered with ethanol and deionized water, and dried to obtain a polyaniline-coated soft magnetic ferrite nanowire precursor.

[0035] Step 3: High-temperature sintering to prepare NiCuZn soft magnetic ferrite nanowires, specifically including: The nanowire precursor obtained in step 2 was placed in a high-temperature sintering furnace for segmented heat treatment: the temperature was increased from room temperature (25℃) to 300℃ at a heating rate of 0.5-1℃ / min and held for 1 hour; then increased to 400℃ at the same rate and held for 2 hours; then increased to 500℃ at a heating rate of 0.5℃ / min and held for 2-4 hours; finally, the temperature was increased to 850℃ at a rate of 1-3℃ / min and held for 1-2.5 hours; after cooling in the furnace, well-crystallized NiCuZn soft magnetic ferrite nanowires were obtained.

[0036] Step 4: Prepare a flexible soft magnetic ferrite composite film, specifically including: 1) The NiCuZn soft magnetic ferrite nanowires obtained in step 3 are uniformly mixed with PDMS prepolymer at a mass fraction of (40-65)% to obtain mixed slurry F, wherein the PDMS prepolymer is composed of basic components and curing agent components in a mass ratio of 10:1. 2) Inject slurry F into the mold and place it in a uniform external magnetic field for 2-4 hours. The magnetic field strength is 0.8-2.0T, so that the nanowires are oriented along the direction of the magnetic field. 3) Transfer the mold to a vacuum drying oven and cure it at 60-80℃ for 2-5 hours. After demolding, you will get a flexible soft magnetic ferrite composite film material for energy storage battery status detection.

[0037] To enable those skilled in the art to fully understand and implement the present invention, the following supplementary description of specific embodiments of the present invention is provided in conjunction with a specific application scenario.

[0038] Example 1 This invention provides a method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection, comprising: Preparation of ultrafine NiCuZn ferrite precursor nanoparticles: ① Accurately weigh five nitrates according to molar percentage: Ni(NO3)2·6H2O (6.3%), Cu(NO3)2·3H2O (6.4%), Zn(NO3)2·6H2O (21.6%), Fe(NO3)3·9H2O (63.8%), and Bi(NO3)3·5H2O (1.2%), and mix them with deionized water. The molar ratio of total nitrates to deionized water is 1:10. Then, slowly add nitric acid solution to adjust the pH of the system to <2. Finally, ultrasonically disperse the nanoparticles at 50℃ for 30 minutes with an ultrasonic power of 200 ppm. W. Obtain a uniform initial mixture A; ② Accurately weigh citric acid according to the molar ratio of citric acid to total metal ions in the initial mixture A of 1.2:1, then dissolve it in deionized water at a molar ratio of 1:3, and add it to the initial mixture A. Subsequently, ammonia water is added dropwise to adjust the pH of the system to 3.0, resulting in mixture B; ③ Accurately weigh V2O5 (0.5%) and CaO (0.2%) according to the molar percentage and add them to mixture B. After uniform dispersion by mechanical stirring, the mixture is stirred and heated at 60℃ for 3 hours to form a sol, and then transferred to a vacuum drying oven for drying to obtain dry gel C at a drying temperature of 80℃ for 4 hours; ④ Sinter the dry gel C at 400℃ for 3 hours, and then treat it with high-energy ball milling to obtain ultrafine NiCuZn ferrite precursor nanoparticles with uniform particle size distribution. The ball milling speed is 1200 r / min and the ball milling time is 4h. This invention obtains ultrafine NiCuZn ferrite precursor nanoparticles with uniform particle size distribution by precisely proportioning nickel nitrate, copper nitrate, zinc nitrate, iron nitrate, and bismuth nitrate, and introducing trace amounts of V and Ca elements for doping, followed by sol formation, drying, sintering, and ball milling.

[0039] Core-shell structured soft magnetic ferrite nanowire precursors were prepared using interfacial polymerization: ① Aniline monomer and ultrafine NiCuZn ferrite precursor nanoparticles were dispersed in cyclohexane to form an oil phase D, wherein the molar ratio of aniline monomer to ultrafine NiCuZn ferrite precursor nanoparticles was 0.8:1; ② Ammonium persulfate was dissolved in deionized water to form an aqueous phase E, wherein the molar ratio of aniline monomer to ammonium persulfate was 1:1.1; ③ The oil phase D was slowly injected into the aqueous phase E to form a clear oil-water interface, and a constant external magnetic field with a field strength of 0.1T was applied at a low temperature of 5℃ and the reaction was allowed to stand for 4 hours; ④ After the reaction was completed, the product was repeatedly washed with ethanol and deionized water, filtered, and dried to obtain polyaniline-coated soft magnetic ferrite nanowire precursors. This invention disperses aniline monomer and ultrafine NiCuZn ferrite precursor nanoparticles in an oil phase, while ammonium persulfate is dissolved in an aqueous phase. An external magnetic field of 0.1T-0.5T is applied at the oil-water interface, and the reaction is allowed to proceed at a low temperature of 0-5℃ for 2-4 hours. The interface confinement effect and the magnetic field-induced effect synergistically promote the formation of core-shell structured nanowire precursors, effectively reducing the risk of disordered particle aggregation.

[0040] High-temperature sintering preparation of NiCuZn soft magnetic ferrite nanowires: The obtained polyaniline-coated soft magnetic ferrite nanowire precursor was placed in a high-temperature sintering furnace for segmented heat treatment: the temperature was increased from room temperature (approximately 25°C) to 300°C at a heating rate of 0.5°C / min and held for 1 hour; then increased to 400°C at the same rate and held for 2 hours; then increased to 500°C at a heating rate of 0.5°C / min and held for 2 hours; finally, the temperature was increased to 850°C at a rate of 1°C / min and held for 1 hour; after furnace cooling, well-crystallized NiCuZn soft magnetic ferrite nanowires were obtained. Building upon the previous step, this invention further integrates this step to achieve precise sintering and successful fabrication of nanowires: employing a four-stage stepped heating heat treatment process: heating to 300℃ at 0.5-1℃ / min and holding for 1 hour → heating to 400℃ at the same rate and holding for 2 hours → heating to 500℃ at 0.5℃ / min and holding for 2-4 hours → heating to 850℃ at 1-3℃ / min and holding for 1-2.5 hours; this precise temperature control ensures good crystallization and structural integrity of the nanowires.

[0041] Preparation of flexible soft magnetic ferrite composite film: ① The obtained NiCuZn soft magnetic ferrite nanowires are uniformly mixed with 45% PDMS prepolymer by mass to obtain mixed slurry F, wherein the PDMS prepolymer is composed of basic components and curing agent components in a mass ratio of 10:1; ② Slurry F is injected into a mold and placed in a uniform external magnetic field with a magnetic field strength of 2.0T for 2 hours to orient the nanowires along the magnetic field direction; ③ The mold is transferred to a vacuum drying oven and cured at 60℃ for 5 hours. After demolding, the flexible soft magnetic ferrite composite film material for energy storage battery state detection is obtained.

[0042] Example 2 This invention provides a method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection, comprising: Preparation of ultrafine NiCuZn ferrite precursor nanoparticles: ① Accurately weigh five nitrates according to molar percentage: Ni(NO3)2·6H2O (6.3%), Cu(NO3)2·3H2O (6.4%), Zn(NO3)2·6H2O (21.6%), Fe(NO3)3·9H2O (63.8%), and Bi(NO3)3·5H2O (1.2%), and mix them with deionized water. The molar ratio of total nitrates to deionized water is 1:10. Then, slowly add nitric acid solution to adjust the pH of the system to <2. Finally, ultrasonically disperse the nanoparticles at 50℃ for 30 minutes with an ultrasonic power of 200 ppm. W. Obtain a uniform initial mixture A; ② Accurately weigh citric acid according to the molar ratio of citric acid to total metal ions in the initial mixture A of 1.2:1, then dissolve it in deionized water at a molar ratio of 1:3, and add it to the initial mixture A. Subsequently, ammonia water is added dropwise to adjust the pH of the system to 3.0, resulting in mixture B; ③ Accurately weigh V2O5 (0.5%) and CaO (0.2%) according to the molar percentage and add them to mixture B. After uniform dispersion by mechanical stirring, the mixture is stirred and heated at 80℃ for 3 hours to form a sol, and then transferred to a vacuum drying oven for drying to obtain dry gel C at a drying temperature of 80℃ for 4 hours; ④ Sinter the dry gel C at 400℃ for 3 hours, and then treat it with high-energy ball milling to obtain ultrafine NiCuZn ferrite precursor nanoparticles with uniform particle size distribution. The ball milling speed is 1200 r / min and the ball milling time is 4h.

[0043] Core-shell structured soft magnetic ferrite nanowire precursors were prepared using interfacial polymerization: ① Aniline monomer and the obtained ultrafine NiCuZn ferrite precursor nanoparticles were dispersed in cyclohexane to form an oil phase D, wherein the molar ratio of aniline monomer to ultrafine NiCuZn ferrite precursor nanoparticles was 1.25:1; ② Ammonium persulfate was dissolved in deionized water to form an aqueous phase E, wherein the molar ratio of aniline monomer to ammonium persulfate was 1:1.1; ③ The oil phase D was slowly injected into the aqueous phase E to form a clear oil-water interface, and a constant external magnetic field with a field strength of 0.5T was applied at a low temperature of 5℃ and the reaction was allowed to stand for 2 hours; ④ After the reaction was completed, the product was repeatedly washed with ethanol and deionized water, filtered, and dried to obtain polyaniline-coated soft magnetic ferrite nanowire precursors.

[0044] High-temperature sintering preparation of NiCuZn soft magnetic ferrite nanowires: The obtained polyaniline-coated soft magnetic ferrite nanowire precursor was placed in a high-temperature sintering furnace for segmented heat treatment: the temperature was increased from room temperature (approximately 25°C) to 300°C at a heating rate of 1°C / min and held for 1 hour; then increased to 400°C at the same rate and held for 2 hours; then increased to 500°C at a heating rate of 0.5°C / min and held for 4 hours; finally, the temperature was increased to 850°C at a rate of 3°C / min and held for 2.5 hours; after furnace cooling, well-crystallized NiCuZn soft magnetic ferrite nanowires were obtained.

[0045] Preparation of flexible soft magnetic ferrite composite film: ① The obtained NiCuZn soft magnetic ferrite nanowires are uniformly mixed with 35% PDMS prepolymer by mass fraction to obtain mixed slurry F, wherein the PDMS prepolymer is composed of basic components and curing agent components in a mass ratio of 10:1; ② Slurry F is injected into a mold and placed in a uniform external magnetic field with a magnetic field strength of 0.8T for 4 hours to orient the nanowires along the magnetic field direction; ③ The mold is transferred to a vacuum drying oven and cured at 80℃ for 2 hours. After demolding, the flexible soft magnetic ferrite composite film material for energy storage battery state detection is obtained.

[0046] Example 3 This invention provides a method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection, comprising: Preparation of ultrafine NiCuZn ferrite precursor nanoparticles: ① Accurately weigh five nitrates according to molar percentage: Ni(NO3)2·6H2O (6.3%), Cu(NO3)2·3H2O (6.4%), Zn(NO3)2·6H2O (21.6%), Fe(NO3)3·9H2O (63.8%), and Bi(NO3)3·5H2O (1.2%), and mix them with deionized water. The molar ratio of total nitrates to deionized water is 1:10. Then, slowly add nitric acid solution to adjust the pH of the system to <2. Finally, ultrasonically disperse the nanoparticles at 50℃ for 30 minutes with an ultrasonic power of 200 ppm. W. Obtain a uniform initial mixture A; ② Accurately weigh citric acid according to the molar ratio of citric acid to total metal ions in the initial mixture A of 1.2:1, then dissolve it in deionized water at a molar ratio of 1:3, and add it to the initial mixture A. Subsequently, ammonia water is added dropwise to adjust the pH of the system to 3.0, resulting in mixture B; ③ Accurately weigh V2O5 (0.5%) and CaO (0.2%) according to the molar percentage and add them to mixture B. After uniform dispersion by mechanical stirring, the mixture is stirred and heated at 80℃ for 3 hours to form a sol, and then transferred to a vacuum drying oven for drying to obtain dry gel C at a drying temperature of 80℃ for 4 hours; ④ Sinter the dry gel C at 400℃ for 3 hours, and then treat it with high-energy ball milling to obtain ultrafine NiCuZn ferrite precursor nanoparticles with uniform particle size distribution. The ball milling speed is 1200 r / min and the ball milling time is 4h.

[0047] Core-shell structured soft magnetic ferrite nanowire precursors were prepared using interfacial polymerization: ① Aniline monomer and the obtained ultrafine NiCuZn ferrite precursor nanoparticles were dispersed in cyclohexane to form an oil phase D, wherein the molar ratio of aniline monomer to ultrafine NiCuZn ferrite precursor nanoparticles was 1.1:1; ② Ammonium persulfate was dissolved in deionized water to form an aqueous phase E, wherein the molar ratio of aniline monomer to ammonium persulfate was 1:1.1; ③ The oil phase D was slowly injected into the aqueous phase E to form a clear oil-water interface, and a constant external magnetic field with a field strength of 0.3T was applied at a low temperature of 5℃, and the reaction was allowed to stand for 3 hours; ④ After the reaction was completed, the product was repeatedly washed with ethanol and deionized water, filtered, and dried to obtain polyaniline-coated soft magnetic ferrite nanowire precursors.

[0048] High-temperature sintering preparation of NiCuZn soft magnetic ferrite nanowires: The obtained polyaniline-coated soft magnetic ferrite nanowire precursor was placed in a high-temperature sintering furnace for segmented heat treatment: the temperature was increased from room temperature (approximately 25°C) to 300°C at a heating rate of 0.8°C / min and held for 1 hour; then increased to 400°C at the same rate and held for 2 hours; then increased to 500°C at a heating rate of 0.5°C / min and held for 3 hours; finally, the temperature was increased to 850°C at a rate of 2°C / min and held for 2 hours; after furnace cooling, well-crystallized NiCuZn soft magnetic ferrite nanowires were obtained.

[0049] Preparation of flexible soft magnetic ferrite composite film: ① The obtained NiCuZn soft magnetic ferrite nanowires are uniformly mixed with 40% PDMS prepolymer by mass fraction to obtain mixed slurry F, wherein the PDMS prepolymer is composed of basic components and curing agent components in a mass ratio of 10:1; ② Slurry F is injected into a mold and placed in a uniform external magnetic field with a magnetic field strength of 1.5T for 3 hours to orient the nanowires along the magnetic field direction; ③ The mold is transferred to a vacuum drying oven and cured at 70℃ for 3 hours. After demolding, the flexible soft magnetic ferrite composite film material for energy storage battery state detection is obtained.

[0050] Comparative Example 1 NiCuZn ferrite was prepared using a classic solid-state sintering method. After ball milling, it was uniformly dispersed in a rubber matrix, and after curing, a flexible NiCuZn ferrite / rubber composite film material was obtained. The specific steps are as follows: The materials were prepared according to the following proportions: CuO 5.1 mol%, NiO 14.3 mol%, ZnO 35.2 mol%, and Fe2O3 45.4 mol%. The mixture was ball-milled with an appropriate amount of deionized water for about 3 hours, followed by pre-calcination at 750℃ for 10 hours. After cooling, 0.3 wt% Bi2O3 and 0.15 wt% V2O5 were added to the pre-calcined material, and the mixture was ball-milled again for about 3 hours. After drying the mixture, 10 wt% polyvinyl alcohol (PVA) was added for granulation, and the mixture was pressed into a green body under a pressure of 5 MPa for 15 seconds. The green body was then sintered at 900℃ for about 3 hours and cooled in the furnace. The sintered NiCuZn ferrite was crushed and ball-milled, dried, and then mixed with 55% NiCuZn ferrite and 45% silicone rubber matrix by mass ratio. The mixture was mechanically stirred to ensure uniform dispersion, and then placed in a vacuum drying oven at 70°C for 3 hours to obtain the conventional soft magnetic ferrite material of Comparative Example 1.

[0051] Comparative Example 2 NiCuZn ferrite was prepared using the sol-gel method, and then dispersed by ball milling and compounded with rubber to obtain a flexible composite film material. The specific steps are as follows: First, the nitrates were accurately weighed according to the molar percentages of Ni(NO3)2·6H2O (6.1%), Cu(NO3)2·3H2O (5.8%), Zn(NO3)2·6H2O (23.5%), and Fe(NO3)3·9H2O (64.6%), and dissolved in an appropriate amount of deionized water. Nitric acid solution was slowly added dropwise to adjust the pH of the system to <2, and the mixture was ultrasonically treated to obtain a homogeneous mixture. Subsequently, citric acid solution was added dropwise to the solution, controlling the molar ratio of citric acid to the total metal ions to be 1.2:1, and then ammonia was added dropwise to adjust the pH to 3.0. The mixture was stirred and heated at 80℃ for 3 hours to form a sol, and after standing for 8 hours, it was transferred to a vacuum drying oven to dry, obtaining a dry gel. The dry gel was sintered at 800℃ for 4 hours and then ball-milled to obtain NiCuZn ferrite powder. Finally, the NiCuZn ferrite powder was mixed with 40 wt% silicone rubber matrix at a ratio of 60 wt%, and after being mechanically stirred to disperse evenly, it was treated in a vacuum drying oven at 80℃ for 2 hours to obtain the conventional soft magnetic ferrite material prepared in Comparative Example 2.

[0052] The NiCuZn ferrite nanowires prepared in Examples 1-3 were tested using scanning electron microscopy, and the results are as follows: Figure 2 As shown, the NiCuZn prepared in Examples 1-3 are all in the shape of nanowire rods and have a large aspect ratio. On the one hand, the large aspect ratio of the nanowires gives them significant shape anisotropy, which is beneficial to greatly improve the magnetic induction performance of the film through directional alignment; on the other hand, the nanowires can play a role similar to fiber reinforcement in composite materials, effectively enhancing the mechanical properties of the film.

[0053] The initial permeability and saturation magnetic flux density of all samples (Examples 1-3 and Comparative Examples 1-2) were measured using an Agilent E4991B radio frequency impedance meter. The results are shown in... Figure 3 The coercivity and power loss of the samples were characterized using an Iwatsu SY8232B-H analyzer, and the corresponding data are as follows: Figure 4 As shown. Furthermore, according to the State Grid Corporation of China enterprise standard "Q / GDW 11304.5—2015" (Technical Specification for High-Frequency Partial Discharge Charge Detection Instruments), the transmission impedance of each sample was tested, and the results are detailed in [link to relevant documentation]. Figure 5 The tensile strength and elongation at break of Examples 1-3 and Comparative Examples 1-2 were tested using a universal testing machine, and the results are as follows: Figure 6 As shown.

[0054] like Figure 3As shown, the flexible soft magnetic ferrite composite thin film materials prepared in Examples 1-3, compared with the magnetic permeability of Comparative Examples 1 and 2, all exhibit saturation magnetic induction greater than 45, while those in Comparative Examples 1 and 2 are less than 40; the initial magnetic permeability of Examples 1-3 is greater than 400, while that of Comparative Examples 1 and 2 is around 200; it is evident that Examples 1-3 demonstrate superior saturation magnetic induction and initial magnetic permeability.

[0055] Figure 4 The comparison of the thin-film soft magnetic ferrite materials of Examples 1-3 with Comparative Examples 1 and 2 in terms of coercivity and power loss is shown. Under the same test conditions, the coercivity and power loss of Examples 1-3 are significantly lower than those of Comparative Examples 1-2.

[0056] According to the State Grid Corporation of China enterprise standard "Q / GDW 11304.5—2015" (Technical Specification for High-Frequency Partial Discharge Charge Detection Instruments), tests were conducted on Examples 1-3 and Comparative Examples 1-2 in the frequency range of 0Hz-100MHz. The results are shown in the table below. Figure 5 The results show that, within this frequency band, the transmission impedance of Examples 1-3 is higher than that of Comparative Examples 1 and 2, and exceeds the 5mV / mA ​​limit specified in the above standard; while the transmission impedance of Comparative Examples 1-2 is lower than this limit at some frequencies, indicating that Examples 1-3 have higher detection sensitivity and can meet the accurate detection requirements of high-frequency current signals of energy storage batteries.

[0057] Figure 6 The comparison of mechanical properties (including tensile strength and elongation at break) between Examples 1-3 and Comparative Examples 1-2 is presented. The flexible soft magnetic ferrite film material prepared using the formulation and process of this invention is superior to the comparative examples in both tensile strength and elongation at break, exhibiting better mechanical properties.

[0058] As is known from common technical knowledge, this invention can be implemented through other embodiments that do not depart from its spirit or essential characteristics. Therefore, the disclosed embodiments described above are merely illustrative in all respects and are not the only ones. All modifications within the scope of this invention or its equivalents are included in this invention.

Claims

1. A flexible soft magnetic ferrite composite thin film material for energy storage battery state detection, characterized in that, It is composed of a magnetic functional phase and a flexible matrix; The magnetic functional phase is NiCuZn soft magnetic ferrite nanowires oriented in a single direction within the flexible matrix. The mass percentage of the NiCuZn soft magnetic ferrite nanowires to the flexible matrix is ​​(40-65)%: (35-60)%.

2. The flexible soft magnetic ferrite composite thin film material for energy storage battery state detection according to claim 1, characterized in that, The flexible matrix is ​​polydimethylsiloxane.

3. The flexible soft magnetic ferrite composite thin film material for energy storage battery state detection according to claim 1, characterized in that, The transmission impedance of the flexible soft magnetic ferrite composite thin film material is greater than 5mV / mA ​​in the range of 0-100MHz.

4. A method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection, characterized in that, include: Preparation of ultrafine NiCuZn ferrite precursor nanoparticles; Using aniline monomer and the ultrafine NiCuZn ferrite precursor nanoparticles as raw materials, and ammonium persulfate as an initiator, a polyaniline-coated core-shell structured soft magnetic ferrite nanowire precursor was prepared by interfacial polymerization reaction at the oil-water interface under the condition of an applied external magnetic field. The core-shell structured soft magnetic ferrite nanowire precursor was sintered at high temperature to obtain NiCuZn soft magnetic ferrite nanowires. The NiCuZn soft magnetic ferrite nanowires are dispersed in a flexible matrix, and an external magnetic field is applied to orient the nanowires. The nanowires are then cured to obtain the flexible soft magnetic ferrite composite film material for energy storage battery state detection. The mass percentage of the NiCuZn soft magnetic ferrite nanowires to the flexible matrix is ​​(40-65)%: (35-60)%.

5. The method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection according to claim 4, characterized in that, The PDMS prepolymer.

6. The method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection according to claim 4, characterized in that, The steps for preparing ultrafine NiCuZn ferrite precursor nanoparticles specifically include: Weigh out nickel nitrate, copper nitrate, zinc nitrate, ferric nitrate, and bismuth nitrate, dissolve them in deionized water, and adjust the pH to below 2 to obtain mixture A; Add an alkaline solution to mixture A to adjust the pH to 3.0, thus obtaining mixture B; Vanadium pentoxide and calcium oxide were added to mixture B, stirred and dispersed, and then heated at 60-80℃ to form a sol. After drying, a dry gel was obtained. The dry gel was sintered and then ball-milled to obtain the ultrafine NiCuZn ferrite precursor nanoparticles.

7. The method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection according to claim 6, characterized in that, The molar percentages of nickel nitrate, copper nitrate, zinc nitrate, iron nitrate, bismuth nitrate, vanadium pentoxide, and calcium oxide are 6.3%, 6.4%, 21.6%, 63.8%, 1.2%, 0.5%, and 0.2%, respectively; the molar ratio of citric acid to the total metal ions in mixture A is 1.2:

1.

8. The method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection according to claim 4, characterized in that, The steps for preparing a polyaniline-coated core-shell structured soft magnetic ferrite nanowire precursor by using aniline monomer and the ultrafine NiCuZn ferrite precursor nanoparticles as raw materials, ammonium persulfate as an initiator, and an interfacial polymerization reaction under the condition of an external magnetic field at the oil-water interface, specifically include: Aniline monomer and the ultrafine NiCuZn ferrite precursor nanoparticles were dispersed in cyclohexane to form an oil phase D; ammonium persulfate was dissolved in deionized water to form an aqueous phase E; the oil phase D was injected into the aqueous phase E to form an interface, and the reaction was allowed to proceed under an external magnetic field of 0.1T-0.5T at 0-5℃ for 2-4 hours; after the reaction, the precursor was washed and dried to obtain the polyaniline-coated core-shell soft magnetic ferrite nanowire.

9. The method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection according to claim 4, characterized in that, In the step of obtaining NiCuZn soft magnetic ferrite nanowires by high-temperature sintering of the core-shell structured soft magnetic ferrite nanowire precursor, the high-temperature sintering is a segmented heat treatment: first, the temperature is increased from room temperature to 300℃ at 0.5-1℃ / min and held for 1 hour; then the temperature is increased to 400℃ at the same rate and held for 2 hours; then the temperature is increased to 500℃ at 0.5℃ / min and held for 2-4 hours; finally, the temperature is increased to 850℃ at 1-3℃ / min and held for 1-2.5 hours; and then the temperature is cooled in the furnace.

10. The method for preparing a flexible soft magnetic ferrite composite thin film material for energy storage battery state detection according to claim 4, characterized in that, The steps of dispersing the NiCuZn soft magnetic ferrite nanowires in a flexible matrix, applying an external magnetic field to orient the nanowires, and then curing them to obtain the flexible soft magnetic ferrite composite film material for energy storage battery state detection specifically include: mixing the NiCuZn soft magnetic ferrite nanowires with a mass fraction of (40-65)% and (35-60)% of the flexible matrix to obtain a mixed slurry; injecting the slurry into a mold and placing it in a uniform external magnetic field of 0.8-2.0T for 2-4 hours to orient the nanowires; then placing the mold in a vacuum drying oven at 60-80℃ for 2-5 hours to cure, and after demolding, obtaining the flexible soft magnetic ferrite composite film material for energy storage battery state detection.